Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (Nht) Terhadap Motivasi Belajar dan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X MAN 2 Model Medan Tahun Ajaran 2024/2025 - Nurhalizah Pasaribu, Gita; Yuni, Revita (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to determine the effect of the Numbered Head Together (NHT) Cooperative Learning Model on Student Learning Motivation and Learning Outcomes in the Economics subject of class X at MAN 2 Model Medan in the 2024/2025 Academic Year. This study was conducted using a quantitative approach with a quasi-experimental method. The population of this study consisted of 179 class X students, and the research sample consisted of two classes, namely the experimental class (X-K) which was given the Numbered Head Together (NHT) learning model treatment and the control class (X-D) which used the conventional learning model. The instruments used were observation sheets to measure learning motivation and test instruments to measure learning outcomes in the form of pre-test and post-test. The instrument feasibility test was carried out through validity and reliability tests. The analysis prerequisite test was carried out with normality and homogeneity tests to ensure the data was normally distributed and homogeneous. Hypothesis testing was carried out with an independent sample t-test. The results of the study showed that there was a significant influence of the Numbered Head Together (NHT) Learning Model on student learning motivation. This was reinforced by the results of the t-test at a significance level of 5% (α = 0.05) with degrees of freedom (df) = 71, obtained t count of 5.176> t table 1.993 and a significance value of 0.000 <0.05. The results also showed that there was a significant influence of the Numbered Head Together (NHT) Learning Model on student learning outcomes, with t count of 4.259> t table 1.993 and a significance value of 0.000 <0.05. Thus, it can be concluded that the Numbered Head Together (NHT) Cooperative Learning Model has an effect on students' learning motivation and learning outcomes in the subject of Economics for class X at MAN 2 Model Medan in the 2024/2025 academic year.